BANK INDONESIA SEBAGAI MEDIATOR DALAM PENYELESAIAN SENGKETA ANTARA BANK DENGAN NASABAH MELALUI MEDIASI PERBANKAN - Intan Puspadewi, Anak Agung Ayu; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
The number of customer complaints not resolved by either making bankIndonesia as the central issuing a policy to provide legal protection of its customers.Banking mediation is one of the alternative dispute resolution of banking with a simple,fast and cheap. This study aims to determine the legal basis of bank Indonesia as amediator in resolving disputes between the bank and the customer through bankingmediation. This study uses the normative method, then the conclusion is bank Indonesiaacts are during mediation institutions have not been established.
Keywords: Banking Mediation, Bank Indonesia, Mediator